Sintesis Natrium Zirkonia Sebagai Katalis Reaksi Transesterifikasi Minyak Goreng Bekas - Agustin, Niyar Candra; Prasdiantika, Ricka (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Catalyst is one of factor that affect the results of the transesterification reaction. Catalyst has spesific properties that can only be used in certain reaction. In order to carry out the transesterification reaction a suitable catalyst is needed and has optimal performance. This research aims to synthesize sodium zirconia (Na2O/ZrO2) as a catalyst for transesterification reaction of used cooking oil into biodiesel and the effect of the concentration of NaOH solution on the zirconia catalyst (ZrO2). The sodium zirconia catalyst(Na2O/ZrO2) was synthesized by wet impregnation method by mixing ZrO2 and NaOH solution with variations in concentrations of 2, 4 and 6 M. Transesterification reaction is carried out with catalyst amount of 5%(w/w), with areaction time of 20 minutes, and by microwave heating at 400 watt microwave power. The comparison of oil molar with methanol was 1:15. Na2O/ZrO2 catalysts was characterized by Fourier Transform Infrared(FT-IR) Spectrophotometer, and X-Ray Diffractometer (XRD) and Scanning Electron Microscopy/Energy Dispersive X-ray (SEM/EDX). The resulting biodiesel was characterized by Gas Chromatography-Mass Spectrometry (GC-MS). Using Na2O/ZrO2 2 M catalysts produced the most biodiesel which was 85.5% (w/w). The formed biodiesel contained methyl palmitate (25,11%), methyl linoleate (10,87%), methyl elaidate (57,88%), and methyl stearate (6,14%). The characterization results showed that Na2O/ZrO2 as the transesterification used cooking oil catalyst was successfully synthesized.